Microhardness and Microstructural Evolution of Pure Nickel Processed by High-Pressure Torsion - Meng Sun; Chaogang Ding; Jie Xu; Debin Shan; Bin Guo; Terence G. Langdon (Crystals, 2023)
High-purity Ni was processed by high-pressure torsion (HPT) at room temperature under an imposed pressure of 6.0 GPa and a rotation rate of 1 rpm through 1/4 to 10 turns, and samples were then examined using Electron Back-Scattered Diffraction (EBSD) and microhardness measurements. The results show that the grain size and low-angle grain boundaries (LAGBs) gradually decrease with the growth of HPT revolutions while the microhardness values gradually increase. After 10 turns of HPT processing, ultrafine-grained (UFG) pure Ni with a reasonable microhardness value and microstructure homogeneity can be achieved across the disk, thereby giving great potential for applications in micro-forming. A grain refinement model for severe plastic deformation (SPD) of pure Ni is proposed.